2021
DOI: 10.1021/acs.chemmater.1c01448
|View full text |Cite
|
Sign up to set email alerts
|

Mode Crystallography Analysis through the Structural Phase Transition and Magnetic Critical Behavior of the Lacunar Spinel GaMo4Se8

Abstract: In the lacunar spinels, with the formula AB 4 X 8 , transition-metal ions form tightly bound B 4 clusters resulting in exotic physical properties such as the stabilization of Néel-type skyrmion lattices, which hold great promise for energy-efficient switching devices. These properties are governed by the symmetry of these compounds with distortion of the parent noncentrosymmetric F 4̅3 m space gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…To further understand the crystal structures, and the effect of pressure, we can consider related chemically substituted systems, the effect of substitution being similar to that of an external pressure. In GaMo 4 Se 8 , when the Jahn-Teller distortion is decomposed into different normal modes, it has been shown that [26] different amplitudes of these modes results in either the F 43m phase (stabilized in GaV 4 S 8 at low P , low T ), or Imm2 phase (stabilized in GaV 4 S 8 at high P , high T ). Further, Ref.…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the crystal structures, and the effect of pressure, we can consider related chemically substituted systems, the effect of substitution being similar to that of an external pressure. In GaMo 4 Se 8 , when the Jahn-Teller distortion is decomposed into different normal modes, it has been shown that [26] different amplitudes of these modes results in either the F 43m phase (stabilized in GaV 4 S 8 at low P , low T ), or Imm2 phase (stabilized in GaV 4 S 8 at high P , high T ). Further, Ref.…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the crystal structures, and the effect of pressure, we can consider related chemically substituted systems, where the effect of substitution is similar to that of an external pressure. In GaMo 4 Se 8 , when the Jahn-Teller distortion is decomposed into different normal modes, it has been shown that [27] different amplitudes of these modes results in either the F 43m phase (stabilized in GaV 4 S 8 at low P, low T ), or Imm2 phase (stabilized in GaV 4 S 8 at high P, high T ). Further, Ref.…”
Section: Resultsmentioning
confidence: 99%
“…polarised neutron-scattering measurements, as well as low-temperature, high-resolution, structural studies to clarify whether the JT distortion drives the compound into a single R 3 m phase or if any additional competing phases are present similarly to what was found in GaMo 4 Se 8 . 28,29…”
Section: Discussionmentioning
confidence: 99%
“…polarised neutron-scattering measurements, as well as low-temperature, high-resolution, structural studies to clarify whether the JT distortion drives the compound into a single R3m phase or if any additional competing phases are present similarly to what was found in GaMo 4 Se 8 . 28,29 Author contributions Jose ´F. Malta: synthesis, characterisation, physical properties measurements, analysis of the results, investigation and writing.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation